ASSOCIATION PHENOMENON AND SIGN - Maftuna Rakhimova (Galaxy International Interdisciplinary Research Journal, 2022)
The associative word and sign (sign) are essentially compatible psycholinguistic terms, and the theory of the linguistic sign is based on the theory of mental association and is formed with the help of it, taking it into its composition.